Extracellular viral microRNAs as biomarkers of virus infection in human cells - Cheryl Chan; Joanne Xin Yi Loh; Wei-Xiang Sin; Denise Bei Lin Teo; Nicholas Kwan Zen Tan; Chandramouli Nagarajan; Yunxin Chen; Francesca Lorraine Wei Inng Lim; Michael E. Birnbaum; Rohan B.H. Williams; Stacy L. Springs (Molecular Therapy: Nucleic Acids)
Nucleic acid amplification tests (NAATs) have enabled fast and sensitive detection of virus infections but are unable to discriminate between live and dead/inert viral fragments or between latent and reactivated virus infections. Here, we show that extracellular viral microRNAs (viral exmiRs) are cell-free candidate biomarkers of live, latent, and reactivated virus infections, achieving fast (under 1 day) and sensitive (30 attomolar [aM]) detection by quantitative real-time reverse transcription PCR (real-time RT-qPCR). We report that spent-media-derived Epstein-Barr virus (EBV) miR-BART10-3p and herpes simplex virus 1 (HSV-1) miR-H5 are biomarkers of live EBV-2 and HSV-1 infection of T cell cultures, respectively. We identified extracellular human herpesvirus 6 (HHV-6) miR-Ro6-4 as a biomarker of endogenous latent HHV-6 in healthy human donor T cell cultures and identified human cytomegalovirus (HCMV) miR-US5-2-5p and miR-US22-5p as plasma biomarkers of endogenous latent HCMV infection. Viral exmiR profiling of spent media from EBV- and HHV-8-reactivated B cell models revealed specific signatures of elevated EBV miR-BHRF1-2-3p and HHV-8 miR-K12-10a-3p, miR-K12-10b, and miR-K12-12-3p, respectively, during virus reactivation. Our study thus suggests the utility of viral exmiR biomarkers in enabling NAAT-based detection of live, endogenous latent, and reactivated virus infections of cells.